Optimasi Kinerja Game 2D pada Platform Mobile dengan Rendering Terbatas - Andini Dwi Lestari; Eva Mirandha Nur Cahya; Khairun Najwa; Retno Dwi Apriliana (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
This abstract presents a systematic literature review on optimizing the performance of 2D games on mobile platforms with limited rendering capabilities. This research is important because smooth performance and energy efficiency are critical challenges in mobile game development. The goal is to identify strategies to overcome the constraints of massive asset loading without reducing frame rates and to balance visual quality with battery consumption. The method used is a systematic review of the latest literature (2021-2025). The results of the study show that a combination of approaches such as multilevel index, prediction-based preloading, energy-aware design, and specialized caching techniques (such as CatNCa) can synergistically maintain performance stability above 30 FPS while optimizing energy efficiency. It is concluded that optimal balance is achieved through the integration of intelligent data scheduling algorithms, motion prediction, and resource-efficient visual design for limited device resources.